The Rotavirus Vaccine Story: From Discovery to the Eventual Control of Rotavirus Disease. (30th September 2021) - Glass, Roger I; Tate, Jacqueline E; Jiang, Baoming; Parashar, Umesh
Abstract: Worldwide, rotavirus is the leading pathogen causing severe diarrhea in children and a major cause of under 5 years mortality. In 1998, the first rotavirus vaccine, RotaShield, was licensed in the United States but a rare adverse event, intussusception, led to its withdrawal. Seven years passed before the next generation of vaccines became available, Rotarix (GSK) and Rotateq (Merck), and 11 years later, 2 additional vaccines from India, Rotavac (Bharat) and Rotasiil (Serum Institute), were recommended by World Health Organization for all children. Today, these vaccines are used in more than 100 countries and have contributed to marked decreases in hospitalizations and deaths from diarrhea. However, these live oral vaccines are less effective in low-income countries with high under 5 years mortality for reasons that are not understood. Efforts to develop new vaccines that avoid the oral route are in progress and will likely be needed to ultimately control rotavirus disease.